Single Input Single Head CNN-GRU-LSTM Architecture for Recognition of Human Activities - Updesh Verma; Pratibha Tyagi; Manpreet Kaur (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Due to its applications for the betterment of human life, human activity recognition has attracted more researchers in the recent past. Anticipation of intension behind the motion and behaviour recognition are intensive applications for research inside human activity recognition. Gyroscope, accelerometer, and magnetometer sensors are heavily used to obtain the data in time series for every timestep. The selection of temporal features is required for the successful recognition of human motion primitives. Different data pre-processing and feature extraction techniques were used in most past approaches with the constraint of sufficient domain knowledge. These approaches are heavily dependent on the quality of handcrafted features and are also time-consuming and not generalized. In this paper, a single head deep neural network-based approach with the combination of a convolutional neural network, Gated recurrent unit, and Long Short Term memory is proposed. The raw data from wearable sensors are used with minimum pre-processing steps and without the involvement of any feature extraction method. 93.48 % and 98.51% accuracy are obtained on UCI-HAR and WISDM datasets. This single-head deep neural network-based model shows higher classification performance over other architectures under deep neural networks.